2007
DOI: 10.1007/s00405-007-0514-7
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of three-dimensional computed tomography of the larynx for evaluation of unilateral vocal fold paralysis before and after treatment: technique and clinical applications

Abstract: Laryngoplasty is well-known technique for unilateral vocal fold paralysis (UVFP). However, operation result are sometimes not as good as expected before surgery. Three-dimensional Computed tomography (3DCT) is useful for visualizing complicated intralaryngeal structures. Moreover, 3DCT is suited for analyzing the movement of the vocal fold and arytenoid cartilage because the technique is based on actual data from live patients. We have been used 3DCT of the Larynx for evaluation of UVFP before and after treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 10 publications
0
32
0
1
Order By: Relevance
“…Therefore, AD can be diagnosed with a complete separation of the joint surfaces on 3DCT during rest and phonation. However, the CAJ capsule is large, and our research has revealed that in cases of severe UVFP, the paralyzed arytenoid cartilage is displaced far from the joint surface in the cranial direction [9,10]. As the finding of arytenoid cartilage displacing partially outside the cricoid facet is common to both severe UVFP [9,10] and AS, the diagnosis of AS requires more detailed observations.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Therefore, AD can be diagnosed with a complete separation of the joint surfaces on 3DCT during rest and phonation. However, the CAJ capsule is large, and our research has revealed that in cases of severe UVFP, the paralyzed arytenoid cartilage is displaced far from the joint surface in the cranial direction [9,10]. As the finding of arytenoid cartilage displacing partially outside the cricoid facet is common to both severe UVFP [9,10] and AS, the diagnosis of AS requires more detailed observations.…”
Section: Introductionmentioning
confidence: 87%
“…Furthermore, a case in which AD and paralysis occur concurrently can only be diagnosed as UVFP when analyzed by electromyography and endoscopy. Reports using CT [1,2,5] have focused on the asymmetry of bilateral arytenoid cartilages, but because the asymmetry is also observed in UVFP [7][8][9][10], one must show the difference between AD/AS and UVFP. In brief, no report to date has clearly demonstrated the optimal strategy for diagnosing AD or AS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is observed regardless of the severity of paralysis. 11,12 It is crucial to eliminate this passive movement so that the vocal folds can develop strong resistance to exhaled airflow and the push from the healthy …”
Section: Meaning Of Arytenoid Adductionmentioning
confidence: 99%
“…6 However, we used three-dimensional CT (3DCT) to study the movement of the arytenoid cartilage and its aid in the diagnosis and treatment. [7][8][9][10] By taking images at appropriate times during phonation and setting thresholds for each, it is possible to construct reproducible 3D images.…”
Section: Introductionmentioning
confidence: 99%